“One Broken Heart / Inside One Whole Heart”: Cyborgian Performances in Efrat Mishori’s Poetry - Arye, Moran (MiKAN, 2022)
The article discusses Efrat Mishori’s early poetry with reference to Donna Haraway’s notion of the cyborg, which she introduced in her formative 1985 essay A Cyborg Manifesto. Active in the Israeli poetry scene since the 1990s, Efrat Mishori offers a methodical and carnivalesque illustration of the desire to make connections in unexpected places, to mix between disciplines, and to propose a generous poetics of contradictory internal experiences and strategies. Referring to Haraway’s notion of the cyborg as a model of multi-channel action, the present article suggests to read Mishori’s poetry as presenting us with a split organism which rather than aiming for harmony and unity, constitutes itself as an event and encodes itself in motion. Looking at two poetry cycli included in Mishori’s first published collection, “She’eylot Im Tshuvot” and “Luakh Hapoel” (Questions with Answers, and The Table of Verbs), I consider manifestations of boundary breaking and the mutual constitution of physical and linguistic bodies, of subject and machine, “broken” and “whole”. The article points at the fracture and conflict at the core of Mishori’s work through their expressions in the psychic, intimate, as well as cultural “operating systems” she describes, situating her cyborg action in the domain between “efficient” functioning, and acts of vandalism and defiance.